Training Of Reading Writing The Qur'an Creating Generation Qur'ani Village Island Nine Substance Pangkalan Susu Langkat District - Ahmad Zaki, Muhammad Saleh, Suaib Lubis, Hayatun Sabariah (International Journal Of Education, Social Studies, And Management (IJESSM), 2021)
The flow of globalization has a positive impact and a negative impact. Advances in technology have brought us ease of activity, but technological advances have also eroded children's lives with the emergence of nature, materialism, capitalism, pragmatism, and hedonism. Children start with bad traits and characters. We are also responsible for the progress of the times by continuing to equip children to continue to be on the correct Islamic corridor. The Qur'anic generation is the generation that uses the Qur'an as a way of life and believes in its truth. They can show strong aqidah, true worship, and good morals, and high civilization. They also read, memorize, and understand properly and correctly the meaning contained in the Qur'an and practice all its contents in aspects of their lives. Thus the community service team for the Islamic Education Management Study Program at the Islamic High School carried out training in reading and writing the Qur'an in Pulau Sembilan Village, Pangkalan Susu District, Langkat Regency. This activity was carried out using the meeting method with the head of Pulau Sembilan Village and MDA teachers, TPQ. Then the training using the lecture method, discussion, and practice. As a result of this activity, the MDA, TPQ teachers were very enthusiastic in participating in this activity. It is proven by the discussions from the participants in honoring the understanding of this training.